Agile Enterprise Architecture – A Literature Review - Luís SILVA RODRIGUES (Communications of International Proceedings, 2022)
There is an increasing interest in adopting such agile practices in all business fields and all aspects of organizations, and Enterprise Architectures (EA) are no exception. Despite the interest of organizations in Agile EA, it isn't easy to find in the literature works that address this topic. To quantify the existing literature on Agile AE, this paper presents the initial results of a systematic literature review, which aimed to clarify the Agile AE concept and to identify the Agile AE frameworks, methods, and models. The systematic literature review followed the PRISMA protocol and was performed on the Web of Science (WOS) database. In this research, only 15 papers were identified. The analysis results show that there is no consensus on the concept of Agile EA and that the proposals presented for frameworks, methods, and models are still in a very early stage and still need to be consolidated and validated.
Keywords: Enterprise Architecture; Agile; Literature Review